Mahdi Poursaberi - Computational Modeling of Cell Behavior Driven by Growth Factor Release from Biodegradable Microcapsules (Jornada de Jóvenes Investigadores del I3A, 2025)
Computational Modeling of Cell Behavior Driven by Growth Factor Release from Biodegradable Microcapsules